Pro/con debate: Continuous versus intermittent dialysis for acute kidney injury: a never-ending story yet approaching the finish? - Vanholder, Raymond (BioMed Central, 2011)
The question of whether renal replacement therapy should be applied in an intermittent or continuous mode to the patient with acute kidney injury has been the topic of several controlled studies and meta-analyses. Although continuous renal replacement therapy (CRRT) has a theoretical advantage due to offering the opportunity to remove excess fluid more gradually, none of the several outcome studies that have been undertaken in the meanwhile was able to demonstrate its superiority over intermittent renal replacement therapy (IRRT). In the present article, therefore, questions are raised regarding which are the specific advantages of each strategy, and which are the specific populations that might benefit from their application. Although several advantages have been attributed to CRRT - especially more hemodynamic stability allowing more adequate fluid removal, better recovery of renal function, and more efficient removal of small and large metabolites - none of these could be adequately proven in controlled trials. CRRT is claimed to be better tolerated in combined acute liver and kidney failure and in acute brain injury. IRRT is more practical, flexible and cost-effective, allows the clinician to discontinue or to minimize anticoagulation with bleeding risks, and removes small solutes such as potassium more efficiently in acute life-threatening conditions. Sustained low-efficiency daily dialysis is a hybrid therapy combining most of the advantages of both options.